A phase II study (WJOG12819L) to assess the efficacy of osimertinib in patients with EGFR mutation-positive NSCLC in whom systemic disease (T790M-negative) progressed after treatment with first- or second-generation EGFR TKIs and platinum-based chemotherapy. (March 2023) - Takeda, Masayuki; Shimokawa, Mototsugu; Nakamura, Atsushi; Nosaki, Kaname; Watanabe, Yasutaka; Kato, Terufumi; Hayakawa, Daisuke; Tanaka, Hiroshi; Takahashi, Toshiaki; Oki, Masahide; Tachihara, Motoko; Fujimoto, Daichi; et al.
Highlights: Osimertinib cannot be used for T790M-negative NSCLC after 1st/2nd generation EGFR-TKI. This study was initiated at the request of a dedicated network for patients with lung cancer in Japan. We demonstrated that osimertinib had modest antitumor activity against those patients. Abstract: Background: Osimertinib is a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) that is an established standard treatment option for chemotherapy-naive patients with EGFR mutation-positive non–small cell lung cancer (NSCLC). However, of such patients who have received prior treatment with a first- or second-generation EGFR TKI, only approximately half are eligible for osimertinib therapy because its indication as second-line treatment and beyond is limited to metastatic NSCLC that is positive for the T790M resistance mutation of the EGFR gene. This study was initiated at the request of a dedicated network for patients with lung cancer in Japan. Methods: We conducted a phase II study to assess the efficacy of osimertinib in patients with EGFR mutation-positive NSCLC in whom systemic disease (T790M-negative) progressed after treatment with first- or second-generation EGFR TKIs and platinum-based chemotherapy. The primary end point was response rate (assessed by a central imaging reviewer). Results: From August 2020 to February 2021, 55 patients from 15 institutions were enrolled in the study. The overall response for primary analysis was achieved in 16 patients (29.1 %; 95 % CI, 17.6–42.9), which exceeded the threshold response rate necessary for analysis. Stable disease was found in 16 patients (29.1 %), and progressive disease, in 18 (32.7 %). The median length of progression-free survival (PFS) was 4.07 months (95 % CI 2.10–4.30), and the rate of 12-month PFS was 17.3 %. Conclusions: Osimertinib demonstrated modest antitumor activity against progressive EGFR T790M-negative disease.